2019
DOI: 10.3390/ijerph16101790
|View full text |Cite
|
Sign up to set email alerts
|

Road Traffic Noise at the Residence, Annoyance, and Cognitive Function in Elderly Women

Abstract: The detrimental effects of traffic noise on cognition in children are well documented. Not much is known about the health effects in adults. We investigated the association of residential exposure to road traffic noise and annoyance due to road traffic noise with cognitive function in a cohort of 288 elderly women from the longitudinal Study on the influence of Air pollution on Lung function, Inflammation and Aging (SALIA) in Germany. Residential noise levels—weighted 24-h mean (LDEN) and nighttime noise (LNIG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 27 publications
0
31
0
3
Order By: Relevance
“…However, at this point, we can offer no clear explanation of these findings. Other authors (22) have also reported significant association between exposure to traffic noise and some CERAD subtests.…”
Section: Overall Findingsmentioning
confidence: 79%
See 2 more Smart Citations
“…However, at this point, we can offer no clear explanation of these findings. Other authors (22) have also reported significant association between exposure to traffic noise and some CERAD subtests.…”
Section: Overall Findingsmentioning
confidence: 79%
“…For instance, Tzivian et al (52) reported positive associations between long-term air pollution and traffic noise exposures and mild cognitive impairment, with some evidence of synergistic effects (53). Another recent study (22) observed inverse relationships between noise levels and total cognition as well as constructional praxis in elderly women tested with CERAD. To our knowledge, only two studies have tested mediation by air pollution/noise; one (51) did not find any such evidence in adults, but the other (34) showed partial mediation by traffic-related air pollution in children.…”
Section: Overall Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lärmbelästigung wird generell als psychische Reaktion auf Lärmexposition angesehen [8] und gilt als umweltbedingte Gesundheitsbelastung. Nach Angaben der WHO ist Lärmbelästigung nach den Schlafstörungen die zweitwichtigste gesundheitliche Auswirkung von Umweltlärm [1] und ist selbst wiederum mit kardiovaskulären Erkrankungen und Beeinträchtigungen der psychischen Ge-sundheit verbunden [7,[9][10][11][12][13][14]. Insbesondere ist bei Lärmbelästigung das Risiko für Bluthochdruck [13], Vorhofflimmern [15], Depressionen und Angststörungen [9] erhöht.…”
Section: Introductionunclassified
“…Nur teilweise ist diese Belästigung durch objektiv messbare Lärmpegel erklärbar. Tatsächlich ist die Korrelation zwischen den objektiven und subjektiven Maßen der Lärmexposition nur moderat, da sie durch regionale und individuelle Faktoren modifiziert werden kann [11,14,[19][20][21][22]. Mehrere Studien zeigten Assoziationen zwischen Lärmbelästigung und regionalen Faktoren wie der Zusammensetzung der Wohngebiete oder -gemeinden bzw.…”
Section: Introductionunclassified